(untitled) (Third Sector Social Economic Review, 2024)
The COVID-19 crisis, which is considered one of the biggest crises in world history, has affected all humanity in terms of health, social life, economy and education. After the virus in Turkey, education and training activities continued in the form of online education. In this period, private educational institutions have undertaken a very important mission in terms of individual and social aspects. In this process, it is known that marketing communication elements have an important contribution to private schools in creating customer satisfaction. In this study, it is aimed to determine the effect of integrated marketing communication elements on customer satisfaction through the example of private schools during the COVID-19 pandemic process. In this context, 389 private school parents in Bursa province were reached via e-mail using convenience sampling and data were collected through a survey application. As a result of the findings obtained, it was determined that there was a significant difference between advertising activities, promotional activities, public relations, distance education process and face-to-face education process and gender, age, educational status and number of children. In addition, a significant effect of integrated marketing communication elements on school satisfaction was determined.